Kontribusi Program Induksi Guru Pemula, Kompetensi Pedagogik, dan Lingkungan Kerja Terhadap Kinerja Guru Di Kabupaten Klaten - Junaedhi, Mufid, Prof.Dr. Budi Murtiyasa, M.Kom, Dr. Suyatmini, M.Si (2016)
Mufid Junaedhi. Q.100140040.The Contribution Of The Beginner Teacher Induction Program,Pedagogy Competency And Working Environment On The Performance Of The Teachers In Klaten Regency. Thesis. Graduate School. Muhammadiyah University Of Surakarta. 2016. This research aims to analyze and measure (1) The contribution of the beginner teacher induction program, pedagogy competency, and working environment on the performance of the teachers. (2) The contribution of the beginner teacher induction program to the performance of the teachers, (3) pedagogy competency contribution to the performance of the teachers, (4) the contribution of the working environment on the performance of the teachersin Klaten regency This research method is quantitative research using descriptive correlational approach. The number of samples in this research was 63 honorary teachers K2 appointed as the government employees in Klaten. The technique of collecting data used proporsional sampling. Data analysis in this research used descriptive statistics test, classical assumptions, multiple regression analysis test, t-test, F-test, determination coefficient (R2),effective and relative contributions. The results of the study showed that: (1) there is a simultaneous contribution beginner teacher induction program, pedagogy competency, and working environment towards the performance of the teachers in Klaten regency with the value of the determination coefficient (R2) about 54,5% with significant level is 0,000 smaller than 0,05, (2) there is a significant contribution to the beginner teacher induction program to teacher performance with effective contribution about 21.4%, (3) there is a significant contribution to pedagogy competency of teacher performance with effective ontribution about 15,95%, (4) there is a significant contribution to the work environment of teacher performance with effective contribution about 17,13 Key words:beginner teacher induction program, pedagogy competency, the working environment , the performance of the teachers.